System throughput versus the transmit power budget, with m = 1, = 0.1, = 0.9 and = 5 [dB]. - Minh Tran (7698803) (2025)
System throughput versus the transmit power budget, with m = 1, = 0.1, = 0.9 and = 5 [dB].